Persuasive Strategies Used by Indonesian’s Presidential Candidate Ganjar Pranowo in His Speech - Lisbeth Sirait; Gunawan Tambunsaribu (Universitas Cokroaminoto Palopo, 2024)
The purpose of this study was to identify the kind of persuasion tactics Ganjar Pranowo employed in one of his political campaign speeches as well as his propensity to do so. This study employed Beebe & Beebe's persuasive strategies theory to examine the data. The data were then subjected to a descriptive-qualitative approach to analysis. Taking notes served as the study team's tool for discovering the most reliable information. The research questions of this study was to gain a deeper understanding of the many persuasive techniques and how they are typically applied in political campaign speeches. The research revealed that Ganjar Pranowo employed various persuasion techniques to gain the audience's or the public's support and buy into his notion. The study came to the conclusion that Ganjar Pranowo employed 14 of the 20 persuasive techniques which are using trustworthiness, giving evidence to tell a story that aid the audience in visualizing what he was describing, using language that elicits feelings, making the right appeals, and showing hope, pride, and courage.